ABUNDANCE AND DISTRIBUTION PATTERN GASTROPODS IN INTERTIDAL ZONE OF TELUK KASAI BEACH PESISIR SELATAN DISTRICT SOUTH SUMATRA PROVINCE - Ide Rival Dianta Sitepu; Afrizal Tanjung; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study aims to determine the abundance, relative abundance and distribution patterns of gastropods in the intertidal zone of the Teluk Kasai beach. This research was conducted in June 2019 in the intertidal zone of the Teluk Kasai beachPesisir Selatan District, West Sumatra Province.The method used in this research is survey method of determining the location of the station using purposive sampling method. Sampling was conducted at random (Random Sampling) using 1x1 m² sized plot. The results were obtained4 species of gastropods from 3 families. Abundance of gastropods are not significantly different. The highest Relative abundance species at all stations which Littoraria scabra. Distribution pattern is clumped. The average temperature values in the range30,6 - 32ºC, salinity in the range of 32 - 33.6 ‰, the degree of acidity (pH) would exist in the range of  7.04 - 7.62, and the total organic material ranges from 3.33 - 4.20%. Type of substrate is Sand Gravely.Keywords: Gastropods, Abundance, Distribution Patterns, Teluk Kasai beach